Complex physicochemical analysis of transformer oil parameters using the inductively coupled plasma mass spectrometry technique - Nurubeyli, T. K.; Hashimov, A. M.; Imamverdiyev, N. E.; Mammadova, G. N. (Національний технічний університет "Харківський політехнічний інститут", 2025)
Transformers are crucial and expensive components of power systems, experiencing electrical, thermal, and chemical stresses. Transformer oil analysis is important for diagnosing transformer faults and assessing its remaining service life. The oil used in transformers degrades over time due to its interaction with electrical loads and heat from the core and windings. The oil degrades into low-molecular gases and carbon particles, which affect its dielectric properties and indicate potential problems. Analysis of dissolved gases in oil allows early detection of defects such as corona or arc discharges, as well as overheating. In addition, analysis of metal content in oil helps to clarify the type and location of the fault identified by gas analysis. Novelty of the proposed work lies in the study of the relationship between transformer oil parameters and its quality, as well as the effect of dissolved gases. The article proposes a method for determining how changes in these parameters affect each other. The obtained data are compared with the results of mass spectrometric analysis for a more accurate assessment of the transformer condition. The purpose of this paper is to explore the connection between the chemical properties of transformer oil and the elemental composition determined through inductively coupled plasma mass spectrometry (ICP-MS). Methods. The solution to the problem was carried out using the inductively coupled plasma mass spectrometry method from Agilent Technologies 7700e (USA) to measure the concentration of metals in transformer oil. Results. An inverse correlation has been identified between the acidity of transformer oil and its furfural content. Experimental evidence has shown that the water content has the most significant impact on decreasing the breakdown voltage of dielectric oil. It was found that CO gas has the greatest influence on the formation of furfural. It has been established that gaseous C2H2 plays an important role in the formation of acidic components. Correlations were found between the oil acidity and the concentrations of copper and iron and between the breakdown voltage and the amount of lead and aluminium in the transformer oil. A high concentration of copper in the oil indicates potential issues with the transformer windings, as well as in any bronze or brass components, and the concentration of iron in significant quantities indicates problems with the transformer core and tank. Moreover, as the breakdown voltage of the oil decreases, there is a marked increase in the concentrations of lead and aluminum. This suggests that significant amounts of lead are found in the transformer solder joints, while aluminum is present in the windings and ceramic bushings.

Трансформатори є важливими та коштовними компонентами енергосистем, які зазнають електричних, теплових та хімічних навантажень. Аналіз трансформаторної оливи важливий для діагностики несправностей трансформатора та оцінки його терміну служби, що залишився. Олива, що використовується в трансформаторах, з часом руйнується через його взаємодію з електричними навантаженнями та теплом сердечника та обмоток. Олива розкладається на низькомолекулярні гази та частинки вуглецю, що впливає на її діелектричні властивості та вказує на потенційні проблеми. Аналіз розчинених газів у оливі дозволяє завчасно виявити дефекти, такі як коронний або дуговий розряд, а також перегрів. Крім того, аналіз вмісту металу в оливі допомагає уточнити тип і місце дефекту, виявленого газовим аналізом. Новизна пропонованої роботи полягає у вивченні зв’язку між параметрами трансформаторної оливи та її якістю, а також впливом розчинених газів. У статті запропоновано метод визначення того, як зміни цих параметрів впливають одна на одну. Отримані дані порівнюються з результатами мас-спектрометричного аналізу для більш точної оцінки стану трансформатора. Метою статті є дослідження зв’язку між хімічними властивостями трансформаторної оливи та елементним складом, визначеним за допомогою мас-спектрометрії з індуктивно зв’язаною плазмою (ICP-MS). Методи. Рішення проблеми здійснювалося за допомогою методу мас-спектрометрії з індуктивно зв’язаною плазмою Agilent Technologies 7700e (США) для вимірювання концентрації металів у трансформаторній оливі. Результати. Між кислотністю трансформаторної оливи та вмістом у ній фурфуролу виявлено зворотну залежність. Експериментальні дані показали, що вміст води має найбільш значний вплив на зниження напруги пробою діелектричної оливи. Встановлено, що найбільший вплив на утворення фурфуролу має газ СО. Встановлено, що в утворенні кислотних компонентів важливу роль відіграє газоподібний С2Н2. Були виявлені кореляції між кислотністю оливи та концентрацією міді та заліза, а також між напругою пробою та кількістю свинцю та алюмінію в трансформаторній оливі. Високий вміст міді в оливі вказує на потенційні проблеми з обмотками трансформатора, а також у будь-яких бронзових або латунних компонентах, а концентрація заліза в значних кількостях вказує на проблеми з сердечником трансформатора та баком. Крім того, у міру зниження напруги пробою оливи спостерігається помітне збільшення концентрації свинцю та алюмінію. Це свідчить про те, що значна кількість свинцю міститься в паяних з’єднаннях трансформатора, тоді як алюміній присутній в обмотках і керамічних втулках.
Keywords: transformer oil; furfural component; breakdown voltage; mass spectrometer; dissolved gases analysis; трансформаторна олива; фурфуроловий компонент; пробивна напруга; мас-спектрометр; аналіз розчинених газів